Medicinal plants as alternative for control of parasites. 3. Arthropods - CHHABRA, M B; MURALEEDHARAN, K; PATHAK, K M L (The Indian Journal of Animal Sciences, 2014)
The control of arthropod (ecto) parasites and disease vectors by use of industrial chemicals being fraught with various problems calls for alternative approaches. Natural products offer world’s resource-poor farmers a cheaper, eco-friendly and sustainable alternative. Ethno-veterinary and traditional knowledge has provided a vast range of plants to be evaluated for their repellent, insecticidal and acaricidal properties. Phyto-chemical analysis of medicinal plants has been increasingly generating evidence of presence of bioactive compounds in extracts derived from them. With the current emphasis on reduction (management) of arthropod numbers to acceptable levels, plant products are likely to play a greater role. A large number of efficacy studies in recent years, both in India and abroad, have validated their bioactivity against various target insects and acarines. These studies covered a wide spectrum of arthropod parasites but mosquitoes and ixodid ticks due to their vector significance attracted maximum attention. The widely prevalent cattle tick Rhipicephalus (Boophilus) microplus appeared to predominate as the most frequent target species. Plant products have considerable potential, which can possibly be further enhanced by improved technology and fine-tuning of delivery systems such as use of nano-capsules and nano-particles. Plant derived acaricides can also be harnessed as a component of an integrated pest management program. In this article, the current state of knowledge on phyto-chemical sources along with their cidal and inhibitory activity on various stages of target insect and acarine species, the nature of active ingredients and promising advances, has been reviewed.